ECOLOGICAL AND HYDROGEOLOGICAL RESEARCH ON "WET" PRESERVATION OF COAL MINES (A CASE STUDY OF ALMAZNO-MAR'YVSKY MINING AND INDUSTRIAL REGION, DONBASS) - Udalov, I.; Chomko, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Goal. The article describes the implications of the Donbass loss-making coal mine removal from service by "wet" preservation. The AlmaznoMar'yvsky mining region (MR) was chosen to be the study area as the most representative of geological complexity, scale of engineering and industrial activities. The main factors in adverse processes and hazards resulting from closing Almazno-Mar'yvsky MR mines have been defined. Methodology. The research yielded data on potential hazards associated with changes in the natural and man-made environment under the mine closure conditions. The results of research. It has been shown that the major effects on the ecology and geology of natural and man-made systems are exerted by ecological and hydrogeological processes accompanied by gas-, mass-, and energy transfer. Data analysis showed that the mine concentration zones had a local man-induced impact on the underground hydrosphere, where a hydrodynamic system formed, with aquifers being interconnected both horizontally and vertically. Originality. The case of closing Proletarskaya mine located in close proximity to the Svetlichansky water intake was used to show the complexity of problems caused by "wet" preservation of coal mines. It has been found that the major changes in the ground water quality at the Svetlichansky water intake resulted from the long-term infiltration of the highly mineralized chloride mine waters from Proletarskaya mine into the aquifer. The mine drainage waters within the Almazno-Mar'yvsky MR were analyzed as well as their implications for balneology. Practical use. The Proletarskaya mine closure has exacerbated gas migration at the Svetlichansky water intake; the presence of radon was detected in the underground water samples. Different aspects have been shown of monitoring the changes in the underground water quality under the conditions of pit closure. The research results may be used as a framework for creating an efficient monitoring system on a local and regional scale.
Keywords: loss-making coal mines; "wet" preservation; hydrodynamic system; Proletarskaya mine; Svetlichansky water intake; AlmaznoMar'yvsky mining region